Processing of Shellfish Shell Waste as Fish and Poultry Feed Ingredients in 3 Shellfish Fisherman Villages in Sidayu District Gresik Regency - Moh. Dian Kurniawan; Hidayat Hidayat (Kontribusia : Research Dissemination for Community Development, 2022)
The use of clam shells through the Community Partnership Program will become a new source of income for shellfish business actors and especially the Sidayu sub-district community can participate in managing and utilizing the abundant shellfish waste to be further processed as a mixture of fish and poultry feed ingredients. Thus, it will increase the income of managers and as a forum for opportunities to support the implementation of the zero waste program in order to create a clean and beautiful sub-district environment. The Community Partnership Program (PKM) through coaching and mentoring contributes to the community with the objectives of: 1. Providing insight or knowledge about the utilization of shellfish waste, 2. Empowering and encouraging the improvement of the welfare of shellfish business actors who are sheltered by the Sidayu MSME Association (ASUMSI) by conduct education as well as training on how to process the use of shellfish as a mixture of fish and poultry feed. The method used is the lecture and question and answer method, giving machines and also demonstrations for processing. Through the PKM Program, it is hoped that good cooperation between partners will be formed in the future in carrying out activities that are to promote MSMEs, and also especially for the community to be able to take advantage of something that used to be waste that has no added value to be processed into a product that has added value and more selling value.